Characterization of Three Functional High-Affinity Ammonium Transporters in Lotus japonicus with Differential Transcriptional Regulation and Spatial Expression - D'Apuzzo, Enrica (American Society of Plant Biologists, 2004)
Ammonium is a primary source of nitrogen for plants. In legume plants ammonium can also be obtained by symbiotic nitrogen fixation, and [Formula: see text] is also a regulator of early and late symbiotic interaction steps. Ammonium transporters are likely to play important roles in the control of nodule formation as well as in nitrogen assimilation. Two new genes, LjAMT1;2 and LjAMT1;3, were cloned from Lotus japonicus. Both were able to complement the growth defect of a yeast (Saccharomyces cerevisiae) ammonium transport mutant. Measurement of [(14)C]methylammonium uptake rates and competition experiments revealed that each transporter had a high affinity for [Formula: see text]. The K(i) for ammonium was 1.7, 3, and 15 μm for LjAMT1;1, 1;2, and 1;3, respectively. Real-time PCR revealed higher expression of LjAMT1;1, 1;2, and 1;3 genes in leaves than in roots and nodule, with expression levels decreasing in the order LjAMT1;1 > 1;2 > 1;3 except in flowers, in which LjAMT1;3 was expressed at higher level than in leaves, and LjAMT1;1 showed the lowest level of expression. Expression of LjAMT1;1 and 1;2 in roots was induced by nitrogen deprivation. Expression of LjAMT1;1 was repressed in leaves exposed to elevated CO(2) concentrations, which also suppress photorespiration. Tissue and cellular localization of LjAMT1 genes expression, using promoter-β-glucuronidase and in situ RNA hybridization approaches, revealed distinct cellular spatial localization in different organs, including nodules, suggesting differential roles in the nitrogen metabolism of these organs.